Development of 3D-printed universal adapter in enhancing retinal imaging accessibility - Aisya Amelia, Abdul Latip; Kuryati, Kipli; Abang Mohammad Nizam, Abang Kamaruddin; Rohana, Sapawi; Kasumawati, Lias; Muhammad Arif, Jalil; Khairul Fikri, Tamrin; Nurul Mirza Afqah, Tajudin; Ong, Han Yi; Muhammad Hamdi, Mahmood; Suriati Khartini, Jali; Siti Kudnie, Sahari; et al. (Springer Nature, 2024)
The revolutionary technology of smartphone-based retinal imaging has been consistently improving over the years. Smartphone-based retinal image acquisition devices are designed to be portable, easy to use, and cost-efficient, which enables eye care to be more widely accessible especially in geographically remote areas. This enables early disease detection for those who are in low- and middle- income population or just in general has very limited access to eye care. This study investigates the limitation of smartphone compatibility of existing smartphone-based retinal image acquisition devices. Additionally, this study aims to propose a universal adapter design that is usable with an existing smartphone-based retinal image acquisition device known as the PanOptic ophthalmoscope. This study also aims to simulate the reliability, validity, and performance overall of the developed prototype.